PEMERTAHANAN BAHASA DAERAH (KODI) PADA ANAK-ANAK SEKOLAH DASAR - Alex Djawa; Labu Djuli; Betharia Pane (Jurnal Lazuardi, 2026)
Maintaining a regional language (Kodi) occurs when the language is used by the community of speakers and their supporters. This regional language continues to be used and preserved because of the process of survival, spread and inheritance. This language survives if it continues to be used by every family member, especially parents who share the same mother tongue, namely Kodi. After that, this language spread by its speakers who always moved to the same environment using the regional language. And this language continues to be passed on to children and grandchildren. This inheritance ensures that this regional language remains sustainable